The liquidity structure of firms and monetary economics - Frazer, William Johnson (Gainesville : University of Florida Press, 1965)
This book examine the liquidity structure of firms and other topics such as motives of holding money, commercial loan doctrine, the income velocity of money and near moneyness, trade credit and monetary policy. It also discuss the wealth and the income velocity of money as well as factors affecting the post war rise in the velocity of money in the United States.
Bibliographical footnotes.
usc 08/10/18
Loans
Keywords: Money; Corporations- finance; United States